Single-stage contralateral total hip and knee arthroplasty: a report of two cases with literature review - Tomar, Lavindra; Govil, Gaurav; Dhawan, Pawan (International Journal of Research in Orthopaedics, 2022)
Total hip arthroplasty (THA) and total knee arthroplasty (TKA) have been performed for end stage degenerative arthritis of hip and knee respectively, with reliable functional outcomes. A single joint arthroplasty has wide acceptance, and presents less complications than a staged or simultaneous bilateral joint arthroplasty. Any contralateral or ipsilateral staged or simultaneous two joint arthroplasty have been infrequently performed and occasionally described. We present two cases where contralateral hip and knee arthroplasty were performed in single-stage simultaneously for an end-stage degenerative arthritis. Hip was operated first than knee in both the cases. The clinical, radiological, and functional recovery was graded good in both. There were no complications, or an extended stay in hospital, and blood transfusion requirements were insignificant. The contralateral two joint arthroplasty needs meticulous preoperative work-up, dedicated high volume joint arthroplasty unit, and use of meticulous standard surgical techniques to achieve the desired functional outcomes.